Evaluación de diferentes niveles de harina de quinua (Chenopodium quinua), en pollos broiler durante la etapa de producción en la provincia de Chimborazo - Rodríguez Arévalo, Andrés Francisco (2022)
The previous investigation was an EVALUATION OF DIFFERENT LEVELS OF QUINOA FLOUR (Chenopodium quinoa), IN BROILER CHICKENS DURING THE PRODUCTION STAGE IN THE PROVINCE OF CHIMBORAZO, parish of San Gerardo, Florida neighborhood. The objectives set in this trial were: to determine the best level of quinoa flour for the production of broiler chickens. Establish in which of the treatments a better productive development is obtained. Analyze the economic benefit/cost relationship. For this investigation, 192 Ross line chickens, 5 days old, were used. The factors under study were: Ross line chickens. Diets formulated with quinoa flour at different levels (10%, 12% and 14%); For the analysis, a DBCA was used and Tukey's functional tests at 5% were performed to compare treatment means and correlation analysis and simple linear regression. The main results obtained were: The optimal dose of quinoa flour + balanced was determined for the growth and development of Ross chickens, by adding 14% (T3); obtaining the highest final average weight of 2538.69 gr/bird; the most efficient feed conversion with a value of 2.02 at the end of the trial and the highest benefit/cost ratio of $1.40; compared to the other treatments.